Analisis Faktor-Faktor yang Mempengaruhi Ekspor Kopi Indonesia dipasar Internasional: Analysis of Factors Affecting Indonesian Coffee Export in the International Market - Febrianti Suherman, Reyhan; Qodarul Hikmah, Suci; Firmansyah, Ricky (JEMeS - Jurnal Ekonomi Manajemen dan Sosial, 2023)
Indonesia is the fourth largest coffee bean producing country in the world after Brazil, Vietnam and Colombia with an average production of 639 thousand tons per year or about 8% of world coffee production. The composition of Indonesian coffee production is 72.84% robusta type coffee and 27.16% arabica type. This study aims to analyze what factors affect Indonesian coffee exports in the international market and the effect of world coffee demand on the volume of Indonesian coffee exports. The research method used is the System Literature Review (SLR) method. The type of analysis in this research is secondary data which processes data from previous journal literature. The results of this analysis of Indonesian coffee exports show that the influence on Indonesian coffee exports is non-economic factors, most of which are from the aspect of production, both domestic and world production so that if production is low, the demand for a product will be difficult to meet, but if production is high, the demand for a product will be met in accordance with the amount requested. Keywords: Export, Indonesian Coffee, Production